Improving the dielectric behavior of NiO nanoparticles by Samarium doping for electromagnetic applications. (16th October 2019) - Al Boukhari, J; Hassan, R Sayed; Awad, R
Abstract: In an attempt to improve the dielectric behavior of NiO nanoparticles, pure and 2% Sm doped NiO nanoparticles were prepared via co-precipitation method. The prepared samples were characterized by x-ray Powder Diffraction XRD and Transmission Electron Microscopy TEM. The XRD results confirm the formation of the NiO cubic structure for both samples and they indicate that the crystallite size of the Sm doped NiO nanoparticles is smaller than that of the pure NiO nanoparticles with comparable lattice parameters. TEM images reveal the formation of weakly agglomerated nanoparticles with size distribution agreeable with the size obtained from XRD results. DC electrical conductivity measurements, recorded in the temperature range 323–573 K, revealed an increase in the dc conductivity with the increase in temperature for both samples. Dielectric measurements were done in the frequency range 50 Hz–5 MHz at different temperatures. The plots of the dielectric constant ε ′, dielectric loss ε ″, loss tangent tan δ and ac conductivity σ ac as a function of both frequency and temperature were discussed. The Nyquist plots, between real and imaginary parts of impedance, were studied at different temperatures. Moreover, the Correlated Barrier Hopping CBH model can describe the conduction mechanism of the prepared samples, and the binding energy Wm and minimum hopping distance Rmin were calculated.